The Influence of Social Media Marketing in Talent Acquisition and Recruitment Students in The Netherlands for Wazza Design Company - Soegoto, Azzahra Trimillennia; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Wazza Design is a start-up consulting company that operates their business in the field of marketing and web design. The company are having partnership with other businesses or known as B2B. Moreover, Wazza Design is a new and young start-up business with less than a year of experience. Currently, the company has a limited amount of capable and qualified personnel in their organization. Apart from the current action done by Wazza Design, the company is still looking forward to adding more talents with various backgrounds of education and experience which could be used to improve Wazza Design’s performance and stimulate growth. In order to attract the potential student talents, the researcher conducted research regarding the strategies that could be implemented by Wazza Design. The method that was used was the qualitative method. Primary data was obtained by spreading the questionnaire and conducting interviews with the students of the Netherlands. As for the Secondary data, it was obtained from reliable sources such as research with similar discussion such as journals, textbooks and theories and credible statistics obtained from Statista.com. Based on the research, the student talents in the Netherlands are using social media platforms to find a job. Therefore 2 strategic recommendations have been created; Optimizing Wazza Design’s Social Media Profile and Using Employer Branding Strategies to Build the reputation of Wazza Design